Social Pharmacy and Clinical Pharmacy-Joining Forces - Anna Birna Almarsdottir; Anne Gerd Granas (MDPI AG, 2015)
This commentary seeks to define the areas of social pharmacy and clinical pharmacy to uncover what they have in common and what still sets them apart. Common threats and challenges of the two areas are reviewed in order to understand the forces in play. Forces that still keep clinical and social pharmacy apart are university structures, research traditions, and the management of pharmacy services. There are key (but shrinking) differences between clinical and social pharmacy which entail the levels of study within pharmaceutical sciences, the location in which the research is carried out, the choice of research designs and methods, and the theoretical foundations. Common strengths and opportunities are important to know in order to join forces. Finding common ground can be developed in two areas: participating together in multi-disciplinary research, and uniting in a dialogue with internal and external key players in putting forth what is needed for the profession of pharmacy. At the end the question is posed, "What's in a name?" and we argue that it is important to emphasize what unifies the families of clinical pharmacy and social pharmacy for the benefit of both fields, pharmacy in general, and society at large.